Prayer - Hallesby, Ole; Carlsen, Clarence J (Minneapolis Augsburg, 1994)
This classic treatise on prayer by one of Norway's leading Christian teachers and devotional writers is a practical and trustworthy guide into a life of friendship with God.
Keywords: Prayer -- Christianity